The king's body : burial and succession in late Anglo-Saxon England - Marafioti, Nicole, 1978- (Toronto Anglo-Saxon series., 2014)
The King's Body investigates the role of royal bodies, funerals, and graves in English succession debates from the death of Alfred the Great in 899 through the Norman Conquest in 1066.